Does the type of treatment have an influence on utility values in a glaucoma population? - Paletta Guedes RA (Dove Medical Press, 2015)
Ricardo Augusto Paletta Guedes,1–3 Vanessa Maria Paletta Guedes,1–3 Sirley Maria Freitas,2 Alfredo Chaoubah1 1Federal University of Juiz de Fora, 2Paletta Guedes Ophthalmological Center, 3Santa Casa de Misericórdia Hospital, Juiz de Fora, MG, Brazil Purpose: To assess the impact of glaucoma therapy on utility values in a glaucoma population. Methods: A cross-sectional study of consecutive glaucoma patients was conducted. Utility values were obtained using the time trade-off method. Visual function variables (visual acuity and mean deviation in the better eye) and sociodemographic and clinical characteristics (age, sex, race, educational level, type of glaucoma, current and past glaucoma treatments, and comorbidities) were also obtained for statistical analysis. We divided the patients into three groups: medical treatment (group 1), surgical treatment (group 2), and mixed surgical and medical treatment (group 3). Results: Mean age of the study population (n=225) was 65.7 years. After controlling for glaucoma stage (early, moderate, and advanced), the difference among the groups in mean utility values was not statistically significant. Number of medications per patient, type of medication, or type of surgical technique did not have an impact on the utility values. Conclusion: Our findings suggest that the type of therapy did not affect the utility values in a glaucoma population. Keywords: quality of life, glaucoma treatment, glaucoma surgery